A new class of amide-based organogels: from oil spill recovery to self-assembly structure analysis. Issue 12 (2nd March 2023) - Yang, Dongdong; Xia, Shuwei; Bao, Mutai; Chen, Xiuping; Kang, Hu; Zhao, Haosen; Li, Yiming
Abstract : H-bonding and van der Waals forces affect the self-assembly between molecules, explaining the self-assembly process of the gel. The spatial configuration of the dimer and the forces between molecules can be visualized through the ESP graph. Abstract : Frequent oil spill accidents not only cause a great loss of energy but also bring about severe ecological risks. Phase-selective organogelators (PSOGs) can selectively solidify oil from oil–water mixtures through the formation of organogels and then the oil can be removed with mechanical tools conveniently. However, the efficient gelation of PSOGs, microscopic self-assembly mechanism of PSOGs in organic solvents and their structure–property relationship are still confusing. In this work, we synthesized three new aromatic amide PSOGs (A18, B18 and A16 ) with different molecular structures and investigated their gelling ability for various organic solvents using rheological tests and SEM images. Importantly, the monomer and dimer structures of the three PSOGs were analyzed using Gaussian 09. Multiwfn and Visual Molecular Dynamics (VMD) were used to obtain their electrostatic potential (ESP) graph. The difference in the properties of A18, B18 and A16 may be determined by FT-IR and XRD. In addition, we know through calculation that A18 and A16 form H-aggregates, while B18 forms J-aggregates, which also reflected the better nature of B18 . These results of theoretical calculations are well consistent with our experimental results and can help us to understand deeply the structure–property relationship of PSOGs.